Help Me to Find A Job: An Analysis of Students' Delivery Strategies In Video Resume - Zuraina, Ali; Amy Zulaikha, Mohd Ali; Shamsul, Harbi; Siti Ainun Jariyah, Hassan; Alia Najaa, Md Nor; Nor Suhardiliana, Sahar (Universiti Teknologi MARA Selangor, 2022)
Delivery strategy is paramount in presentations regardless it is employed using video recording or live presentation. Nevertheless, demonstrating appropriate delivery strategies is challenging for many presenters, mainly when video recorded. The present study analyses tertiary level students' delivery strategies when they were required to prepare video resumes. More specifically, the objectives of the study are to identify intonation, body language and creativity that the students demonstrated in preparing the materials. Using descriptive research design, the study analysed 21 video resumes, specifically evaluating students' delivery strategies. The results of the study showed that there were challenges in using intonation and demonstrating appropriate body language among the students during the recorded presentation. The study also found that students tended to be less creative since they had limitations in using resources to prepare the video resumes. The study implies that students need to sharpen their delivery strategies as preparing effective video resumes may provide better employment chances.